RESEARCH STUDIES CONDUCTED ON THE USE OF DIGITAL TECHNOLOGIES IN DEVELOPING STUDENTS’ CREATIVE ABILITIES IN TECHNOLOGY EDUCATION CLASSES AND THEIR ANALYSIS - Safarova Sevara Salokhiddinovna (International Journal of Literature and Language Studies, 2026)
This article provides a scientific and methodological analysis of the role and effectiveness of digital technologies in developing students’ creative abilities in technology education classes. In the modern educational process, digital tools such as 3D modeling software, graphic design applications, interactive design platforms, online constructors, and simulations facilitate the stimulation of students’ technical creativity, the formation of design thinking, and the development of creative approaches to solving practical problems. The article systematically examines national and international research conducted on the subject. Comparative analyses of experimental studies, pedagogical projects, and the impact of software tools on various components of creativity are presented. The findings indicate that the systematic use of digital technologies significantly enhances students’ abilities to generate independent and non-standard solutions, engage in design and modeling activities, and create products that are both aesthetically and technically sound.